On regulation and competition: Pros and cons of a diversified monopolist - Carlo Scarpa; Giacomo Calzolari (Fondazione Eni Enrico Mattei (FEEM), 2009)
We study the regulation of a firm which supplies a regulated service while also operating in a competitive, unregulated sector. If the firm conducts its activities in the two markets jointly, it enjoys economies of scope whose size is the firm's private information, unknown either to the regulator or to the rival firms. We characterize the unregulated market outcome (with price and quantity competition) and optimal regulation that involves an informational externality to the competitors. Although joint conduct of the activities generates scope economies, it also entails private information, so that regulation is less efficient and the unregulated market too may be adversely affected. Nevertheless, we show that allowing the firm to integrate productions is (socially) desirable, unless joint production is characterized by dis-economies of scope.
Keywords: L51; L43; L52; 330; Regulation; Competition; Asymmetric Information; Conglomerate Firms; Multiutility; Scope Economies; Informational Externality